Optimalisasi Kecepatan Jelajah Berbasis Indeks Biaya dalam Pelatihan Penerbangan: Studi pada Cessna 172SP di Akademi Penerbang Indonesia Banyuwangi - Rochmad Setiawan; Prasetyo Iswahyudi; Ahmad Mubarok; Imam Fadila (BADAN PENERBIT STIEPARI PRESS, 2025)
In general aviation (GA) training, particularly on piston engine aircraft such as the Cessna 172 SP, cruising speed decisions are typically based on established standard procedures or instructor judgment, without economic calculations. This study introduces the Cost Index General Aviation (CIGA), adapted from airline operations, to enable more accurate and data-driven cruising speed selection. The study uses operational data from the Indonesian Civil Pilot Academy, Banyuwangi, and applies multiple linear regression (MLR), sensitivity analysis, and descriptive analytics to model the relationship between flight time, fuel consumption, and operating costs. CIGA is the ratio of the cost of time (instructor wage per hour) to the price of fuel, expressed in liters per hour. This index acts as a dynamic decision threshold: when the additional fuel burn per hour from a higher cruising speed is less than the CIGA value, flying at a higher speed is more cost-effective; when it exceeds the CIGA, flying at a slower speed is more economical. This study simulated flight patterns at various engine rpm levels between 2200 – 2650 rpm and found that 2400 rpm provided optimal performance under balanced operating conditions. A sensitivity analysis showed that fuel price had the greatest impact on profitability, followed by instructor wages and maintenance costs. The results indicate that the CIGA system can be a practical decision support tool for mangerial, finance, instructors and operators, offering cost savings of up to 12% per sortie for training purpose. This research contributes to the development of cost-effective, data-driven operations in the general aviation training environment.